Organics and biofertilizers in improving the yield and quality of black pepper - Filitte Stephen (Department of Plantation Crops and Spices, College of Horticulture, 2002)
An investigation was carried out at the College of Horticulture, Vellanikkara during 2000-2001 to study the influence of organics and biofertilizers on yield and quality of black pepper varieties Panniyur 1 and Panniyur 2. The salient findings are abstracted below: Vegetative characters except number of leaves per lateral did not show significant effect of applied organics and biofertilizers. Fresh and dry yields of berries per vine as well as drying percentage of berries also failed to produce any significant difference among treatments. With respect to quality attributes like essential oil, oleoresin and piperine contents, an integrated nutrient management with biofertilizer + organic + inorganic combination was found significantly superior. In general, treatments involving complete orgaruc and biofertilizer + organic + inorganic combinations exhibited higher values of all soil nutrients except S, Ca and Zn. Foliar N, P and K contents recorded higher values with FYM + inorganic treatments while Ca and S uptake were better with biofertilizer treatments. Uptake of Mg and micronutrients exhibited no significant treatment differences. Biofertilizer applied plots registered higher soil microbial population of fungi, bacteria and actinornycetes. Significant positive correlations with yield were exhibited by plant height, canopy spread, number of laterals, number of spikes, spike length and number of berries per spike in both the varieties. Higher benefit cost ratio was recorded by control plots in both the varieties. Excluding control, most economic treatments were T 6 (FYM + 50% Nand 100% P and K as inorganic) and T9 (all the three biofertilizers + FYM + NPK as inorganic) in Panniyur 1 (BCR - 2.52) and T, (FYM + biofertilizer + inorganic combination) in Panniyur 2 (BCR - 3.92).